The Monetary and Macroeconomic Conditions on Interest Rate Spread: Empirical evidence from Indonesia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
This study examines the Interest Rate Spread (IRS) in Indonesia which is influenced by monetary instrument variables, macroeconomic conditions, and event structural changes (Asian Crisis, Global Financial Crisis, COVID-19 and Election year). The analytical method used is the Autoregressive Distributed Lag (ARDL) Model with data observations from 1990 - 2021. The purpose of this study is to determine the strength of the IRS on economic conditions in Indonesia. The results of the analysis show that in the long run, M2, total credit and inflation have a negative effect on the IRS variable, while the household consumption variable has a positive effect. The policy implications need to be applied in efforts to control the IRS are related to monetary policy.